Undifferentiated Chordae Tendineae of the Mitral Valve: Large Cohort Study of a Rare Mitral Malformation - Pang, Kunjing; Wang, Jingjin; Zhang, Tingting; Wu, Jinlin; Gao, Yiming; Liang, Yu; Ma, Kai; Mao, Fengqun; Pan, Xiangbin; Hu, Shengshou; Li, Shoujun (Frontiers in Cardiovascular Medicine, 2021)
Aims This study aimed to investigate the pathology, classification, diagnosis, and surgical prognosis of UCMV. Methods and Results Consecutive paediatric patients with ≥ moderate-severe mitral regurgitation (MR) and mitral stenosis (MS) were recruited between October 2016 and July 2020. UCMV was diagnosed and classified into three grades according to the involvement of chorda groups and MS presence or absence; other mitral lesions were included as controls. Of 207 eligible patients, 75 with UCMV (10.0 m [interquartile range (IQR): 6.0–21.5]) and 110 with other mitral lesions (16.0 m [IQR:5.0–43.5]) were diagnosed using echocardiography and surgical exploration. The associated chorda groups of UCMV were confirmed to show high agreement between echocardiography and surgery (kappa=0.857, p<0.001). At baseline surgery assessment, the UCMV group exhibited worse New York Heart Association functional class, more severe MR and MS grades, and fewer associated complex anomalies (all, p<0.05) than the control group. After a mean follow-up of 8.3 (IQR:2.7–14.4) months and adjustment for covariates, the UCMV group required longer cardiopulmonary bypass and aortic clamp times, but there were no differences in the incidence of adverse events (p=0.584). Class III was associated with higher risk of adverse events than classes I and II (p=0.002). Conclusions The UCMV spectrum constitutes a primary pathogenesis of paediatric MV dysfunction, which can be optimally diagnosed using echocardiography. Classification based on mitral anatomy and dysfunction can predict the risk of postoperative adverse events.